Social workers' desk reference - Corcoran, Kevin (Kevin J.); Roberts, Albert R. (Oxford University Press USA, 2015)
People all over the world are confronted by issues such as poverty, a lack of access to quality education, unaffordable and or inadequate housing, and a lack of needed health and mental services on a daily basis. Due to these issues, there is a need for social workers who have access to relevant and timely scholarly materials in order to meet the needs of those facing these issues. The social, psychological, and biological factors resulting from these issues determine the level of a person's mental health at any given point in time and it is necessary for social workers to continue to evolve a.